Case report: One case of refractory membranous nephropathy with hypokalemia after rituximab infusion was switched to obinutuzumab without recurrence of hypokalemia - Zhang, Yao; Sun, Jing; Gao, Jie; Sun, Weiyan; Xu, Liang; Zhai, Chunjuan; Su, WenYan; Wang, Haiping (Frontiers in Pharmacology, 2024)
Rituximab (RTX) is a monoclonal antibody commonly used to treat PLA2R-associated membranous nephropathy (MN). This report presents a case of refractory MN in a patient who experienced severe hypokalemia, a rare but clinically significant condition, after the 5th RTX infusion. Clinicians should be aware of the potential for hypokalemia and its management during or after RTX infusion. After the onset of hypokalemia, the patient received treatment with obinutuzumab and achieved partial remission of renal disease without experiencing further hypokalemia. Obinutuzumab may be a viable alternative therapy for refractory membranous nephropathy that develops side effects after rituximab therapy or is refractory to it, but further studies are necessary to determine its efficacy and safety.